Sheep feeding preference as a tool to control pine invasion in Patagonia: influence of foliar toughness, terpenoids and resin content - Zamora Nasca, Lucía Belén (2020)
Herbivores modulate the structure and composition of plant communities, including plant invasions. This is conditioned by plant palatability which can be reduced by its chemical or physical traits. The effects that ungulates browsing has on pine invasions are variable and the empirical evidence on the causes of this variability is scarce. We experimentally explored how sheep browsing preference varies between seedlings of pine species with different invasiveness; Pinus contorta (high invasiveness), P. ponderosa (medium invasiveness), P. radiata (medium invasiveness) and P. jeffreyi (low invasiveness). Secondly, we quantified anti-herbivory chemical compounds and physical traits of these species and related them with sheep preference observed. The browsing incidence of P. contorta was 68%, P. ponderosa 58%, P. radiata 29%, and P. jeffreyi 84%. Among anti-herbivory traits analyzed, α-pinene concentration had a negative effect on the probability of a terminal bud being browsed and on browsing intensity. Meanwhile, foliar toughness was negatively related to browsing intensity and water concentration was positively related to browsing intensity. Also, the most invasive species, P. contorta, was highly damaged. Thus, sheep herbivory could be slowing pine invasion rate; suggesting that could be considered a tool to control early invasions, especially for this particular species.